EFEKTIVITAS EDU GAME BERBASIS GIMKIT UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS VIII SMP NEGERI 1 BARANTI - Syafiqah; Syamsunir; Takdir, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Effectiveness of Gimkit-Based Edu Games to Improve Science Learning Outcomes for Class VIII SMP Negeri 1 Baranti". Supervised by Muhammad Takdir and Syamsunir. This research aims to determine the effectiveness of using Gimkit-based edu game learning media in improving science learning outcomes for class VIII students at SMP Negeri 1 Baranti. The research method used is quantitative with a deductive approach. This type of research is quasi experimental with a one group pretest posttest design. This research did not use a control group, but compared student learning outcomes before and after using Gimkit media. Data was collected through pretest and posttest. Data analysis uses descriptive statistics and significance tests. The research results showed that there was a significant increase in student learning scores using Gimkit, from an average pretest score of 41.83 increasing to 80.11 in the posttest, with a significance value of 0.000 < 0.05. Thus, it can be concluded that the use of Gimkit-based edu games is effective in improving students' science learning outcomes.